The gay and lesbian literary heritage a reader's companion to the writers and their works, from antiquity to the present - Summers, Claude J. (Routledge, 2013)
"The Gay and Lesbian Literary Heritage, Revised Edition, provides expanded overviews of gay and lesbian literatures from an array of historical periods; international coverage, including in-depth critical essays on gay and lesbian authors in world literature from an international selection of scholars; and thorough treatment of topics and figures vital to understanding the complexity and diversity of gay and lesbian literary traditions. Included are more than 380 alphabetically arranged articles, each with cross-references and bibliography." --Book Jacket.